Battered Baby Syndrome: A Barbaric Act - Singh, Rajendra; Sharma, Yogesh; Mathur, P N; Khatri , Nimish (Journal of Indian Academy of Forensic Medicine, 2015)
Battered baby syndrome is a heinous crime and brutish act. Knowledge of such cases gives us  the thought that we are still living in barbaric era. By the thought of such cases one gets goose bumps.  The battered child refers to the child usually less than three years of age, though it may occur at any age,  who suffers repeated non- accidental injuries, sometime fatal, caused through episodes of violence by a  parent or guardian. Physicians have a duty and responsibility to the child to require a full evaluation of the  problem and to guarantee that no expected repetition of trauma will be permitted to occur. Forensic  expert also has an important role to play in uncovering the cases of battered baby syndrome. We present  two incidences of battered baby syndrome aged 12 year and 5 year. The first was a male child who  committed suicide by hanging after beaten repeatedly by her mother. The second case was a female  child, admitted in our hospital pediatrics side beaten repeatedly by her father.
Keywords: Battered baby syndrome; Crime; Trauma; Suicide